A fundamental connection: Exchange rates and macroeconomic expectations - Vania Stavrakeva; Jenny Tang (Federal Reserve Bank of Boston, 2020)
This paper presents new stylized facts about exchange rates and their relationship with macroeconomic fundamentals. We show that macroeconomic surprises explain a large majority of the variation in nominal exchange rate changes at a quarterly frequency. Using a novel present value decomposition of exchange rate changes that is disciplined with survey forecast data, we show that macroeconomic surprises are also a very important driver of the currency risk premium component and explain about half of its variation. These surprises have even greater explanatory power during economic downturns and periods of financial uncertainty.
Keywords: E44; F31; G14; G15; 330; exchange rates; exchange rate disconnect; macroeconomic announcements; international finance; professional forecast